Two Aquaporin Genes, GhPIP2;7 and GhTIP2;1, Positively Regulate the Tolerance of Upland Cotton to Salt and Osmotic Stresses - Guo, Anhui; Hao, Jianfeng; Su, Ying; Li, Bin; Zhao, Nan; Zhu, Meng; Huang, Yi; Tian, Baoming; Shi, Gongyao; Hua, Jinping (Frontiers in Plant Science, 2022)
Aquaporins (AQPs) facilitate the transport of water and small molecules across intrinsic membranes and play a critical role in abiotic stresses. Here, 111, 54, and 56 candidate AQP genes were identified in Gossypium hirsutum (AD1), G. arboreum (A2) and G. raimondii (D5), respectively, and were further classified into five subfamilies: plasma intrinsic protein (PIP), tonoplast intrinsic protein (TIP), nodulin 26-like intrinsic protein (NIP), small basic intrinsic protein (SIP), and uncategorized X intrinsic protein (XIP). Transcriptome analysis and Quantitative Real-time PCR (qRT-PCR) revealed some high-expression GhPIPs and GhTIPs (PIP and TIP genes in G. hirsutum, respectively) in drought and salt stresses. GhPIP2;7-silenced plants decreased in the chlorophyll content, SOD activity and POD activity comparing the mock control (empty-vector) under 400 mM NaCl treatment, which indicated a positive regulatory role of GhPIP2;7 in salt tolerance of cotton. The GhTIP2;1-silenced cotton plants were more sensitive to osmotic stress. GhTIP2;1-overexpressed plants exhibited less accumulation of H2O2 and malondialdehyde but higher proline content under osmotic stress. In summary, our study elucidates the positive regulatory roles of two GhAQPs (GhPIP2;7 and GhTIP2;1) in salt and osmotic stress responses respectively, and provides new gene resource for future research.